Hubungan Pola Makan dengan Kejadian Kekurangan Energi Kronik pada Ibu hamil di Desa Sanankerto Kecamatan Turen - Heppy Sri Pratikasari; Rosyidah Alfitri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the relationship between dietary patterns and the incidence of Chronic Energy Deficiency (CED) among pregnant women in Sanankerto Village, Turen District. Poor dietary habits in terms of quantity, quality, and frequency of food intake can lead to insufficient energy intake during pregnancy, increasing the risk of CED. This research employed a descriptive quantitative approach with a comparative design involving 30 pregnant women divided into intervention and control groups. Data were collected through structured questionnaires and analyzed using an Independent T-Test with a significance level of 0.05. The results showed that the intervention group, which received nutritional education, had significantly higher diet scores compared to the control group, with a significance value of p = 0.000. These findings indicate that nutritional education interventions have a positive effect on improving the quality of dietary intake and reducing the risk of CED. Therefore, nutrition-based interventions should be integrated into maternal health services, especially in rural communities, to prevent CED and associated pregnancy complications.